Controllability approach to H ∞ control problem of linear time-varying switched systems - P. Niamsup (2018)
This paper considers a H∞control problem of a class of linear uncertain time-varying switched system via controllability approach. We show that the solution of this problem can be verified by the global null-controllability of linear control systems. The feedback stabilizing controllers for the problem are constructed via the solutions of certain Riccati differential equations. © 2008 Elsevier Ltd. All rights reserved.